Integrasi Sociopreneurship dalam Pendidikan Kesejahteraan Sosial: Analisis Kebutuhan dan Model Kurikulum di Perguruan Tinggi Islam Indonesia. - Budi Rahman Hakim; Supardi Uki Sajiman; Fajrur Rahman (Lembaga Pengembangan Kinerja Dosen, 2024)
The employment crisis of higher education graduates, the low relevance of the curriculum, and the need for community empowerment encourage the importance of transforming social education based on values ​​and local contexts. This study aims to explore the integration of the sociopreneurship approach in social welfare education in Indonesia, especially in State Islamic Universities (PTKIN). Using an explorative-critical literature study method, this study examines the theoretical framework, international curriculum practices, and recommends a contextual curriculum model based on Islamic values ​​and community empowerment. The results show that the sociopreneurship curriculum can increase active student participation, strengthen social character, and create sustainable solutions to welfare challenges. The integration of Islamic values ​​such as justice, maslahat, and social responsibility is an important moral foundation in the development of this curriculum. This study recommends designing a project-based curriculum, multi-sector involvement, and support for higher education policies as prerequisites for implementing the model systematically.